Social Empowerment for People with Disability as Aceh Social Department Responsibility - Nilda - Mutia; Iskandar A Gani; Mahdi Syahbandir (Universitas Syiah Kuala, 2021)
The aims of this study is to analyze the implementation of empowerment by the Aceh Social Department for people with disabilities and the obstacles in its implementation, in accordance with government regulation No. 52 year 2019 about the welfare accomplishment for people with disabilities.This legal study employs the juridical-empirical method using primary data gathered from interviews and secondary data from literature review as supporting material. Afterward, the data is analyzed using a qualitative approach.The findings showed that the Aceh Social Service based on the Minister of Social Affairs Regulation No. 9 year 2018 concerning Basic Service Technical Standards on a Minimum Service Standardsin the Social Sector in Province and Regency/City only authorized to implement the empowerment for the disabled who were in the orphanage, where, Aceh currently has only one orphanage under Aceh Social Service which available special for the disabled-blind. The obstacles in its implementation are inaccurate data available, limited budget and limited human resources, resulted the empowerment has not implement optimally. A systematic planning and mapping should be done by related party, with the aim, every type of disability can be reached and the efforts can be performed properly, until the independent and the inclusive people with disabilities/disabled groups can be achieved.